Hadith #45 - Jami' al-Tirmidhi - Isma'il bin Musa al-Fazari al-Siddi إسماعيل بن موسى الفزاري السدي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Thabit bin Abi Safiyya ثابت بن أبي صفية (Jami' al-Tirmidhi)
“I asked Abu Ja’far: ‘Did Jabir narrate to you that: “The Prophet performed Wudu one time each, and two times, and three times?” He said: “Yes.”
Grade:

Hadith #46 - Jami' al-Tirmidhi - Thabit bin Abi Safiyya ثابت بن أبي صفية (Jami' al-Tirmidhi)
“1 asked Abu Ja’far: ‘Did Jabir narrate to you that: “The Prophet performed Wudu one time each?” He said: “Yes.”
Grade:

Hadith #1789 - Jami' al-Tirmidhi - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amir al-Sha'bi عامر الشعبي; Thabit bin Abi Safiyya ثابت بن أبي صفية; Umm Hani bint Abi Talib (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) arrived in Makkah, and he had four braids.” This Hadith is Hadith Gharib. ‘Abdullah bin Abi Najih is from Makkah, and Abu Najih’s name is Yasar.
Grade: